Association of non-selective β blockers with the development of renal dysfunction in liver cirrhosis: a systematic review and meta-analysis - Xiangbo Xu; Fangbo Gao; Ting Wang; Zuyao Yang; Qingchun Zhao; Xingshun Qi (Annals of Medicine)
Background & Aims Non-selective β blockers (NSBBs) may negatively influence renal function through decreasing heart rate and cardiac output. This study aimed to systematically investigate their association.Methods PubMed, EMBASE, and Cochrane library databases were searched to identify all relevant studies evaluating the association of NSBBs with renal dysfunction in cirrhotic patients. Unadjusted and adjusted data were separately extracted. Odds ratios (ORs) and hazard ratios (HRs) were pooled. Subgroup meta-analyses were performed according to the proportions of ascites and Child-Pugh class B/C and the mean model for end-stage liver disease (MELD) score. Quality of evidence was assessed using the Grading of Recommendations Assessment, Development, and Evaluation framework.Results Fourteen studies were finally included. Based on unadjusted data, NSBBs significantly increased the risk of developing renal dysfunction (OR = 1.49; p = 0.03), and this association remained significant in subgroup analyses of studies where the proportions of ascites was >70% and Child-Pugh class B/C was 100%. Based on adjusted data with propensity score matching (adjusted OR = 0.61; p = 0.08) and multivariable regression modelling (adjusted HR = 0.86; p = 0.713), NSBBs did not increase the risk of developing renal dysfunction, and this association remained not significant in subgroup analyses of studies where the proportions of ascites was >70% and <70%, the proportion of Child-Pugh class B/C was <100%, and the mean MELD score was <15. The quality of evidence was very low for all meta-analyses.Conclusions NSBBs may not be associated with the development of renal dysfunction in liver cirrhosis. However, more evidence is required to clarify their association in specific populations.